Energy-Aware Routing Architecture for Wireless Sensor Networks - Boyaci, Aytug; Balik, Hasan Huseyin; Ata, Fikret (IEEE, 2022)
The resources used for WSNs are typically limited, and it is essential for these limited resources to be used effectively within scope of the architectural structure. This study suggests an efficient routing architecture. Two environments, consisting of a simulation program and an experimental set, were used in order to demonstrate the performance offered by the suggested routing architecture. The first step to developing applications on WSNs is acquisition of results through implementation of the work on a simulation program. Following a successful outcome from the work carried out on the simulation program, it is essential for the system to be tested on an experimental set in order to confirm the validity of the results. The accuracy of the results yielded by the suggested routing architecture's design is tested in two stages. The first stage involves acquisition of results through the experimental setup. The second stage consists of acquisition of simulation program results for the same number of nodes, followed by a comparison of both result sets.
Keywords: wireless sensor network; energy awareness; routing architecture; Computer Science